PSYCHODYNAMIC FEATURES OF THE SUBJECT OF AN INFOKOMMUNIKATION WITH HIGH LEVEL OF A NEVROTIZATION - TatyanaVictorovna Belyh (Вестник Северо-Кавказского федерального университета, 2022)
In article the interrelation of level of a nevrotization and psychodynamic properties of the personality defining features of realization of process of an infokommunikation is analyzed.